2010
DOI: 10.1182/blood-2010-02-269746
|View full text |Cite
|
Sign up to set email alerts
|

Complement inhibition decreases the procoagulant response and confers organ protection in a baboon model of Escherichia coli sepsis

Abstract: Severe sepsis leads to massive activation of coagulation and complement cascades that could contribute to multiple organ failure and death. To investigate the role of the complement and its crosstalk with the hemostatic system in the pathophysiology and therapeutics of sepsis, we have used a potent inhibitor (compstatin) administered early or late after Escherichia coli challenge in a baboon model of sepsis-induced multiple organ failure. Compstatin infusion inhibited sepsis-induced blood and tissue biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
160
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 161 publications
(179 citation statements)
references
References 38 publications
(48 reference statements)
8
160
1
2
Order By: Relevance
“…C5a up-regulates tissue factor and PAI-1 (37) on monocytes, thereby enhancing blood thrombogenicity and decreasing dissolution of fibrin clots (38). We previously demonstrated that C3 inhibition reduced thrombocytopenia and microvascular thrombosis, and preserved endothelial anticoagulant properties (15). Here we show that C5 inhibition also substantially decreases the activation of both intrinsic and extrinsic pathways of coagulation, as well as the fibrinolytic system in septic baboons.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…C5a up-regulates tissue factor and PAI-1 (37) on monocytes, thereby enhancing blood thrombogenicity and decreasing dissolution of fibrin clots (38). We previously demonstrated that C3 inhibition reduced thrombocytopenia and microvascular thrombosis, and preserved endothelial anticoagulant properties (15). Here we show that C5 inhibition also substantially decreases the activation of both intrinsic and extrinsic pathways of coagulation, as well as the fibrinolytic system in septic baboons.…”
Section: Discussionmentioning
confidence: 56%
“…Similar to C3 inhibition (15), blocking C5 ameliorated sepsisinduced cardiomyopathy, one of the main predictors of poor outcome in septic patients. C5a is a major cardio-depressant (41).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations